RANCANG BANGUN SISTEM PENDETEKSI KEBAKARAN DINI BERBASIS LOGIKA FUZZY MENGGUNAKAN MULTISENSOR - Nur Yanti; Fathur Zaini Rahman; Taufik Nur (Journal of Industrial Engineering Management, 2019)
At Indonesia, cases of residential house fires are still rampant. This resulted in considerable losses for the population of Indonesia. If there is no prevention or countermeasure, it is possible that the danger of a house fires will continue. Therefore, this system exists to create a condition where the system is able to detect the potential that will bring a fire hazard. In this system using a method that is the application of a multisensory system in detecting the presence of fire, smoke and temperature in the room. The sensors used include KY-026 fire sensor, MQ-9 smoke sensor and DS18B20 temperature sensor. Then the system also implements an intelligent system that is fuzzy logic to process sensor reading data. The three sensor inputs will be processed through the fuzzification stage, rule evaluation and the deffuzification. The output of this system is in the form of firm values, namely the values 1 to 5 from the results of the multisensory defuzzification in each module. So the error of the defuzzification average is 0.99% after being compared with the MATLAB output. This system is expected to be able to provide early warning of the threat of fire, reduce the risk of casualties, and be able to be implemented to a wider scale or scope.